Development of an attitude control system for the SCOOB-II satellite - Kostrzewa, Mateusz (Nanyang Technological University, 2021)
Spacecraft attitude control is a non-trivial problem which involves merging knowledge from fields of rigid body dynamics, control theory, and embedded systems. Solution to this problem enables extends satellite’s capabilities in orbit and helps meet complex mission objectives. An Attitude Control System (ACS) was developed to meet performance requirements of the Satellite Research Centre’s SCOOB-II mission. A 3DoF dynamic simulation of the 3U satellite system was created for that purpose. Quaternion notation was used to represent attitude. Appropriate actuators were chosen according to maximum external disturbance torque calculations. Models of actuators were integrated into the simulation. Based on simulated system dynamics a PD controller was fit to generate actuator commands from an attitude control error. The system was tuned to meet the mission’s performance requirements. Results of the simulation provided insight into how an idealised system would respond to attitude changes in orbit. Different attitude manoeuvres were simulated to confirm robustness, reliability, and stability of the control system. Response time for most significant attitude changes did not exceed 10 seconds and had negligible steady state error. Physical actuators were then tested and characterized to confirm their adherence to the system and its requirements. The results of testing yielded a delay of around 0.3 seconds in reaction wheel motors’ response to commands. Magnetic torque rods were found to fully comply with the 0.2 A-m¬2 magnetic dipole moment as stated in their datasheet. Torques imparted by both reaction wheels and magnetic torquers met the performance needs of ACS. Basic functionality of the system was then successfully tested on a dedicated ACS PCB with physical actuators.